Seasonal variation of water discharge and suspended sediment concentration of the Pinios River (Thessaly) during the hydrological year 2012/13 - Lazogiannis, K.; Paraskevopoulou, V; Poulos, S.; Teou, X; Kotsopoulos, S; Farsirotou, E.; Ghionis, G.; Matiatos, I.; Panagopoulos, A; Sifnioti, D.E.; Giannouli, D.I.; Tsanakas, K.; et al. (12th International Conference on Protection and Restoration of the Environment, 2014)
The current study examines flow (Q) and suspended sediment concentration (SSC) variations, based on monthly snapshots, of the Pinios River (Thessaly), which is one of the larger rivers in Greece, characterized by limited flow control (<10% of its catchment). Monthly measurements (flow velocities and water samples) during the hydrological year (October 2012 to September 2013) were conducted at two stations; one before the river enters its delta (Agia Paraskevi bridge at Tempi) and one close to its mouth (Palaiopyrgos bridge). Monthly flows at Agia Paraskevi range from 2.5 m3 /s to 206.7 m3 /s and are in a good agreement with available historical data for the period 1975/76- 93/94, indicating a rather unchanged flow regime. The SSC values ranged from 3.5 mg/L to 165 mg/L at Agia Paraskevi and from 2.2 mg/L to 177 mg/L at Palaiopyrgos and, in general, follow the monthly trend of flow. The highest SSC value measured in February and April 2013 is attributed to a flood event and an upland slide, respectively.